Aesthetic guidance and its Civilizational dimensions according To Malek ben Nabi - Amine KENANE (Social Sciences Journal, 2021)
The study aims to clarify the beautiful concept according to Malek Ben Nabi that exceeds the limits of sensory emotions and aesthetic perceptions to moral and educational dimensions, this is what summarized by the idea of ​​aesthetic guidance which is considered as social education.Ben Nabi acknowledges the deviation of the beautiful concept as a result of cultural confiscations known by the Muslim individual, as it is assured at the levels of proof that the idea of ​​guidance is recuperation all the cultural, ethical and aesthetic components. so, the principle of aesthetic guidance aims to build a specific purpose of the aesthetic perceptions, which is an ethical goal that is mainly related to the religious idea, the later makes the Muslim individual moving to the stage of civilization.